Potensi Permainan Papan Edukasi Aktif Kutus PHBS Sebagai Modalitas Pencegahan Obesitas Anak - I Gusti Ayu Amanda Sinta Adhi Putri; Elvina Veronica; Frisilia Olivia; Martin Rinaldi Pasaribu; Ni Ketut Sutiari (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; lifestyle changes and lack of information about PHBS (The Clean and Healthy Behavior) or balanced nutrition are triggers for obesity. Purpose: To determine the potential of active education cutus board games for clean and healthy behavior to prevent obesity in children. Methods: Study literature articles in the last 10 years using keywords accessed from the Cochrane browser, NCBI, Google scholar, and Garuda. Result; Clean and Healthy Behavior active education board game is easy to play, cheap, has 2-way interaction and has a learning pattern by doing where children are required to find solutions when playing. Conclusion; The educational board game cutus active Clean and Healthy Behavior improves children's knowledge and behavior to prevent obesity in children